The Effect of Gamma Irradiation on Ethanolic Extract of Temulawak (Curcuma xanthorrhiza Roxb.) Against Human Cancer Cell Lines - Susanto Susanto; Ermin Katrin Winarno; Hendig Winarno (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2021)
The Effect of Gamma Irradiation on Ethanolic Extract of Temulawak (Curcuma xanthorrhiza Roxb.) Against Human Cancer Cell Lines. One of the medicinal plants that are widely used by the people of Indonesia is temulawak (Curcuma xanthorrhiza Roxb.) with the active ingredient is curcuminoid. The curcuminoid is a yellow compound that is believed to have anti-cancer properties, therefore its properties must be maintained in the post-harvest process. This research aimed to study the effect of gamma irradiation on the simplicia of C. xanthorrhiza rhizomes in inhibiting the proliferative activity against human cancer cell lines. The dry powder of C. xanthorrhiza rhizome was irradiated with gamma at a dose of 10 kGy in 2 replications, then extracted using ethanol solvent, evaporated, to obtain an ethanol extract. As a control, an un-irradiated sample was prepared and extracted in the same manner. Each ethanol extract from irradiated and control samples was then tested for their antioxidant activity by DPPH method and antiproliferative activity against human cancer cell lines (HUT78, A549, HeLa, and THP1). The results showed that the ethanol extract of irradiated C. xanthorrhiza rhizome with a dose of 10 kGy still had antioxidant activity and anticancer properties based on the bioassay against four those human cancer cell lines, although the antiproliferative activity decreased between 8-30% compared to the control sample. The highest antiproliferative activity was shown by the ethanol extract against HUT78 cancer cell line with IC50 values of 5.4 and 10.7 µg/ml for control and irradiated samples respectively. Based on the silica gel TLC plate, the ethanolic extracts of C. xanthorrhiza rhizome both unirradiated- and irradiated samples contained curcumin (Rf = 0.58) and demethoxycurcumin (Rf = 0.38).